Beyond Narrow Confines: Special Education Leadership for Ethnically Diverse Urban Learners - Gathogo Mukuria; Festus E. Obiakor (Educational Considerations, 2006)
Human frailties exist in everyone. There are some things that we know and some that we do not know.
Keywords: Urban School; environment; diverse; learners; education; leadership